PENGARUH KEPUASAN PERITEL, REPUTASI PERUSAHAAN DAN KOMITMEN TERHADAP HUBUNGAN JANGKA PANJANG PADA PRODUK (AMDK) GALON MEREK AQUA DI KECAMATAN WELAHAN KABUPATEN JEPARA (Students' Journal of Economic and Management, 2015)
This study aims to examine and analyze the influence of retailer satisfaction, corporate reputation and commitment to long term relationships to AMDK products Aqua  brand gallonsatsub-district Welahan Jepara regency. This research used several analysis tools, such as the validity test, reliability, regression analysis and coefficient of determination to test the proposed hypothesis.   The population in this study are AMDK Aqua brand gallons retailers in sub-district Welahan Jepara regency.There are66retailersAMDK Aqua brand gallons in this study, wheresampling method used was “purposive sampling” with the criteria : retailers in sub-district Welahan Jepara regency were becomig a retailer of at least one year. The results ofthis study indicatethatthere was apartialypositiveand significantinfluenceofvariablesRetailersatisfaction, Corporate reputation andCommitment toLong term relationshipat AMDK products Aqua  brand gallonsin sub-district Welahan Jepara regency. The variable that gave most influencing on long term relationship wasRetailer satisfaction, then followed by Commitment and Corporate reputation. Keywords: Retailer satisfaction, Corporate reputation, Commitment and Long term relationship